Community effectiveness of pyriproxyfen as a dengue vector control method: A systematic review. - Dorit Maoz; Tara Ward; Moody Samuel; Pie Müller; Silvia Runge-Ranzinger; Joao Toledo; Ross Boyce; Raman Velayudhan; Olaf Horstick (Public Library of Science (PLoS), 2017)
Vector control is the only widely utilised method for primary prevention and control of dengue. The use of pyriproxyfen may be promising, and autodissemination approach may reach hard to reach breeding places. It offers a unique mode of action (juvenile hormone mimic) and as an additional tool for the management of insecticide resistance among Aedes vectors. However, evidence of efficacy and community effectiveness (CE) remains limited.The aim of this systematic review is to compile and analyse the existing literature for evidence on the CE of pyriproxyfen as a vector control method for reducing Ae. aegypti and Ae. albopictus populations and thereby human dengue transmission.Systematic search of PubMed, Embase, Lilacs, Cochrane library, WHOLIS, Web of Science, Google Scholar as well as reference lists of all identified studies. Removal of duplicates, screening of abstracts and assessment for eligibility of the remaining studies followed. Relevant data were extracted, and a quality assessment conducted. Results were classified into four main categories of how pyriproxyfen was applied: - 1) container treatment, 2) fumigation, 3) auto-dissemination or 4) combination treatments,-and analysed with a view to their public health implication.Out of 745 studies 17 studies were identified that fulfilled all eligibility criteria. The results show that pyriproxyfen can be effective in reducing the numbers of Aedes spp. immatures with different methods of application when targeting their main breeding sites. However, the combination of pyriproxyfen with a second product increases efficacy and/or persistence of the intervention and may also slow down the development of insecticide resistance. Open questions concern concentration and frequency of application in the various treatments. Area-wide ultra-low volume treatment with pyriproxyfen currently lacks evidence and cannot be recommended. Community participation and acceptance has not consistently been successful and needs to be further assessed. While all studies measured entomological endpoints, only two studies measured the reduction in human dengue cases, with inconclusive results.Although pyriproxyfen is highly effective in controlling the immature stages of dengue transmitting mosquitoes, and-to a smaller degree-adult mosquitoes, there is weak evidence for a reduction of human dengue cases. More well designed larger studies with appropriate standardised outcome measures are needed before pyriproxyfen is incorporated in routine vector control programmes. Additionally, resistance to pyriproxyfen has been reported and needs investigation.